Shape-controlled metal oxides for selective catalytic oxidation - Burange, Anand S.; Gopinath, Chinnakonda (Advanced Heterogeneous Catalysts Volume 1: Applications at the Nano-Scale, 2020)
Some of industrial processes involve selective oxidation reactions that include the use of corrosive and nonbenign oxidants and solvents. Many metal oxide-based catalysts have been reported for selective oxidation processes, and they exhibit a range of activities compared to homogeneous protocols and current practices. To bridge the gap between homogeneous and heterogeneous catalysis in terms of activity and selectivity and move toward green oxidation processes, this chapter discusses the shape-controlled synthesis of a selected range of metal oxides and their applications in selective catalytic oxidation reactions. This chapter also discusses some of the interesting micro- and nanostructured materials used in these reactions, as well as the roles of exposed predominant facets, defects, and other features and their effects on catalysis. Oxides of Mn, Co, Ce, Cu, Fe, La, and some combinations thereof are presented. Chemical reactions such as the selective oxidations of alcohol, ethyl benzene, styrene, xylene, and 5-hydroxymethylfurfural and the preferential oxidation of CO are also discussed.